Student’s perceptions towards working in the tourism industry / Tuan Nurlaila Tuan Kob,Fauziah Mat Nawi and Hasyifa Mohamed Arif - Tuan Kob, Tuan Nurlaila; Mat Nawi, Fauziah; Mohamed Arif, Hasyifa (2014)
Poor image and lack of understanding on job offer has long been debated in the tourism industry. Although various initiatives has been taken to educate and train future tourism graduates, one can never deny important of understanding student perceptions and attitudes towards working in the Tourism industry. The purpose of this study is to identify and investigate the perceptions and attitudes career in hospitality and tourism industry among undergraduate students in Universiti Teknologi Mara, Kampus Bandaraya Melaka. To undertake these students were asked to identify which factors were important when choosing a career. Additionally, students were asked their perception towards a number of dimensions relating career in the Hospitality and Tourism industry. The population of this study is focus on all students of Hotel and tourism management from semester two (2) until semester six (6). The sample of this study is focus on students from semester two (2) and semester six (6).